Evaluation of the effects of clearing agents, fixation, and process durations on cardiovascular tissue imaging with second harmonic generation and multi-photon modalities - Makki, Maedeh; Molander, Zachary A.; Pineda-Castillo, Sergio A.; Laurence, Devin W.; Singhal, Shubhra; Eltwafsha, Yasmin; Holzapfel, Gerhard A.; Gu, Tingting; Lee, Chung-Hao (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionProtocols for tissue clearing have been established and optimized for the central nervous system. However, significant modifications are required for clearing different tissue types. Therefore, effective optical clearing for cardiovascular tissue remains a major challenge. The goal of this study is to better understand the responses of porcine left anterior descending artery (LADA) to label-free multiphoton imaging.MethodsTo this end, the effects of different clearing methods (i.e., benzyl alcohol benzyl benzoate–BABB and glycerol), formalin fixation, variations in formalin fixation times (0–240 min), and extended storage in BABB (up to 14 days) are investigated. We compare tissue characteristics under different conditions (e.g., tissue clearing reagent and/or tissue fixation), particularly with regard to tissue preservation and transparency across z-stacks (i.e., imaging depths).ResultsThe glycerol clearing method exhibited relatively lower tissue transparency, whereas BABB increased mean AF-AUC from 0.0035 ± 0.0009 to 0.1205 ± 0.0168 and SHG-AUC from 0.0003 ± 0.0002 to 0.0072 ± 0.0040 (p< 0.001), enabling robust signal intensities at deeper layers of LADA tissue. In addition, we observed that BABB preserves fluorescent signals even after extended tissue storage with no significant loss in integrity over 14 days. Finally, we found that formalin fixation in combination with the glycerol clearing method significantly improved tissue preservation compared to the glycerol clearing method alone. However, in combination with the BABB clearing method, fixation reduced tissue transparency and signal intensity compared to BABB clearing without fixation.DiscussionThese findings establish BABB as the superior, label-free clearing agent for deep 3D multiphoton microscopy/second harmonic generation imaging of cardiovascular tissue and underscore the necessity of tailoring fixation parameters to the chosen clearing method.